Foliar epidermal micromorphology and its taxonomic significance in Polygonatum (Asparagaceae) using scanning electron microscopy. Issue 11 (12th July 2020) - Ali, Maroof; Bahadur, Saraj; Hussain, Abrar; Saeed, Sara; Khuram, Izaz; Ullah, Manzoor; Shao, Jian‐Wen; Akhtar, Naveed
Abstract: In the current investigation, 16 samples of six species of the genus Polygonatum were collected from different geographical regions in China. Leaf micromorphological traits were studied in detail using scanning electron microscopy. About five‐leaf samples were used for each species collected from different geographical regions. A significant variation was found in the foliar epidermal traits such as stomata types and their distribution, epidermal cell shape, anticlinal wall pattern, and various types of trichomes. Polygonal epidermal cells were observed in P. cyrtonema, P. odoratum, P. sibiricum, and P. filipes, rectangular in P . zanlanscianense and P. odoratum and irregular shape in P. filipes and P. zanlanscianense . Straight anticlinal wall pattern was observed in most of the species, but straight to little undulate was observed in P. cyrtonema, P. filipes, and P. zanlanscianense . Similarly, various shape stomata that are, oval, oblong, and elliptical and types that is, paracytic, anomocytic, and actinocytic have been observed. Based on the foliar traits, the P. odoratum and P. sibiricum were found closely related to one another. On the other hand, P. involucratum and P. zanlanscianense shows a strong association . However, P. filipes showed very less similarity with the other five species. Hence this study adds useful information that may be helpful in the further taxonomic classification of the taxa at subspecies level and was found significant in the correct identification and discrimination of the closely related taxa of the genus Polygonatum . Abstract : Foliar epidermal traits and its taxonomic potential value in the genus Polygonatum (Asparagaceae) have been studied. Scanning electron microscopy was used as a tool in the identification and discrimination of the Polgonatum taxa. A comprehensive study of the Polygonatum was documented to strengthen the taxonomy of the genus.